اﻵﺛﺎر اﻟﻨﻔﺴﯿﺔ واﻻﺟﺘﻤﺎﻋﯿﺔ ﻟﻠﻌﻨﻒﺿﺪ اﻟﻤﺮأة (Journal of the College of Education for Women, 2019)
The research consists of an introduction, the research dilemma, the importance & the aims and then the two chapters of the research. The first chapter titled "The Concept VIOLENCE AGAINST WOMEN" contains types &essence of violence, stages of marital violence & rough husband characteristics while the practical side containsdetection,the results of analysisandconclusions. The second chapter titled "THE PSYCHOLOGICAL & SOCIAL EFFECTS OF VIOLENCE AGAINST WOMEN" contain several aspects that women face and suffer psychologically because of it. The third chapter represents the practical aspect and contains detection form with several questions deals with the subjects of the research and then the results of analysis. The research concluded that woman is not equivalent with man and she faces violence to all of her rights. The writer affirmed on the role of media to decrease the phenomena of violence against women and to establish a radio station specified on women issues and deals with theirs problems and makes solutions and also produce development chances and to educate society that violence has many effects and losses continued to the coming generations. The research also affirms on writing thesis and researches on this phenomena in order to specify its reasons, types and how to solve it. The writer depended on several resources in accomplishing this research .